PENGARUH BUDAYA ORGANISASI, KOMPETENSI, DAN MOTIVASI KERJA TERHADAP KINERJA TENAGA PRAMUBAKTI DENGAN MENGGUNAKAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL INTERVENING - Diah Asdiany; Muammar Khaddafi; Sapar Sapar (Kelola: Journal of Islamic Education Management, 2022)
Employee performance is the works result or work performance of employees both individually and in groups within a certain time which is assessed based on the quality and quantity of work produced. This study aims to determine the effect of organizational culture, competence, and work motivation on the performance of service staff using information technology as an intervention variable at IAIN Palopo. This study uses quantitative methods, the research population is 52 people who are also respondents. Data analysis used Structural Equation Model (SEM) with the help of SMART PLS 3 software. The results showed that (1) organizational culture, competence, and work motivation variables had no significant effect on the performance of service workers, (2) work motivation variables had a significant effect on the use of Information Technology, (3) the variable of using Information technology has a significant effect on performance, (4) Indirectly, work motivation has a positive and significant effect on the performance of service workers through the use of information technology.